Mapping Cyberspace - Dodge, Martin; Kitchin, Rob (Routledge, 2001)
Mapping Cyberspace is a ground-breaking geographic exploration and critical reading of cyberspace, and information and communication technologies. The book: * provides an understanding of what cyberspace looks like and the social interactions that occur there * explores the impacts of cyberspace, and information and communication technologies, on cultural, political and economic relations * charts the spatial forms of virutal spaces * details empirical research and examines a wide variety of maps and spatialisations of cyberspace and the information society * has a related website at http://www.MappingCyberspace.com. This book will be a valuable addition to the growing body of literature on cyberspace and what it means for the future. Martin Dodge is a researcher and computer technician at the Centre for Advanced Spatial Analysis, University College, London. Rob Kitchin is a lecturer in Human Geography at the National University of Ireland, Maynooth. 'Mapping Cyberspace is an important pioneering work. The authors have performed a valuable service and have produced an essential reference for anyone seriously interested in the spatial, social, economic and cultural implications of telecommunications infrastructure and cyberspace.' - William J Mitchell, Environment and Planning 'The book provides a clear and broad introduction to major theoretical. Methodical, and empirical issues related to cyberspace research. Mapping Cyberspace is a critical first stop for any researcher interested in contributing new knowledge in this exciting emerging field.' - Joshua Lepawsky, University of Kentucky for Cultural Geographies